The Brand Image Of Tebing Tinggi City On Government Public Relations’ Social Media: Efforts To Maintain Its Status As The “City Of Lemang” - Putri, Ainisa; Sazali, Hasan (UNIVERSITAS PAKUAN, 2025)
Tebing Tinggi City in North Sumatra has a close history with the Padang Kingdom and Datuk Bandar Kajum, which later developed into a city with a distinctive culinary identity, namely lemang. Since being introduced by the Minangkabau ethnic group in 1947, lemang has become a widely known city icon, even getting the nickname